Evaluation of a Medical course program using the logic module (Research, Society and Development, 2022)
This article presents the evaluation of educational programs, more precisely the logical evaluation model, Context a Input a Process a Product (CIPP), to verify the quality of teaching and learning in the medical course of a public institution in the interior of Minas Gerais. Thus, the study aimed to evaluate the educational program of the medical course of a public institution in the interior of Minas Gerais using the Logical Model or CIPP instrument. For this, an analysis was carried out of the National Curriculum Guidelines (DCN) of Medicine Courses, the Pedagogical Project of the Course (PPC), the minutes of the Structuring Teaching Nucleus (NDE) and later data surveys were carried out from the interviews with the technicians, student and course teachers. The logical model analyzed the medical course program pointing to issues that promote better teaching-learning for students and structural issues that need to be improved in the municipality and in the higher education institution.